Examining fundamental movement competency and closed-chain upper-extremity dynamic balance in swimmers - Bullock, G. S.; Brookreson, N.; Knab, A. M.; Butler, R. J. (The Journal of Strength and Conditioning Research, 2017)
Abnormal fundamental movement patterns and upper-quarter dynamic balance are proposed mechanisms affecting athletic performance and injury risk. There are few studies investigating functional movement and closed-chain upper-extremity dynamic stability in swimmers. The purpose of this study was to determine differences in fundamental movement competency and closed-chain upper-extremity dynamic balance, using the Functional Movement Screen (FMS) and Upper-Quarter Y Balance Test (YBT-UQ), of high school (HS; n = 70) and collegiate (COL; n = 70) swimmers. Variables included the individual movement tests on the FMS and the average normalized reach (percent limb length [%LL]) for each direction, with the YBT-UQ. Statistical analysis was completed using a chi square for the independent test scores on the FMS while independent samples t-test to examine performance on the YBT-UQ (p = 0.05). HS swimmers exhibited a statistically significant greater percentage of below average performance (score of 0 or 1) on the following FMS tests: lunge (HS: 22.9%, COL: 4.3%), hurdle step (HS: 31.4%, COL: 7.1%), and push-up (HS: 61.4%, COL: 31.4%). Furthermore, COL males performed worse in the lunge (male: 9%, female: 0%), whereas COL females had poorer efficiency in the push-up (male: 17.6%, female: 44%). Significant effects of competition level and sex were observed in YBT-UQ medial reach (HS: female 92.06, male 101.63; COL: female 101.3, male 101.5% LL). Individual fundamental movement patterns that involved lumbopelvic neuromuscular control differed between HS and COL swimmers. General upper-extremity dynamic balance differed between competition levels. These data may be helpful in understanding injury and performance-based normative data for participation and return to swimming.